Association between the Taq1A polymorphism and problematic media use in preadolescent children - Emond, Jennifer A.; Renier, Timothy J.; Yeum, Dabin; Carlson, Delaina D.; Ballarino, Grace A.; Gilbert-Diamond, Diane (Frontiers in Psychology, 2025)
ObjectiveProblematic media use (PMU) is addiction-like media use. No study has examined if genetic factors for addiction relate to PMU during childhood. This study tested the association between genetic risk factors for addiction and PMU among 9-to-12-year-olds.MethodData were from a cohort of 9-to-12-year-olds recruited from Northern New England, 2018–2022, for a study examining obesity risk among children. Two polymorphisms related to dopaminergic (ANNK1 rs1800497 [the Taq1A polymorphism] and COMT rs4680) and one related to nicotinic (CHRNA4 rs1044396) pathways that were previously associated with internet addiction or internet video game addiction in adolescents and young adults were genotyped. Parent-reported PMU for children was measured with a validated nine-item scale (range for final scores: 1 to 5); higher scores indicate more severe PMU.ResultsAmong children (n = 180; 43.9% female; 90.0% white, non-Hispanic; 82.2% of parents were college graduates), the median PMU score was 2.22 (IQR: 1.78, 2.78). In a linear regression model adjusted for child age, sex, European ancestry, and parent education, there was an additive association between the number of Taq1A1 alleles and PMU among children. Specifically, geometric mean PMU scores were 8.6% greater for each additional copy of the Taq1A1 allele (p = 0.030; R2 = 5.2%). No other polymorphisms were statistically associated with PMU at the p < 0.05 level.ConclusionThese preliminary findings suggest that a genetic predisposition to reduced dopamine sensitivity as indicated by the Taq1A polymorphism may relate to PMU in early adolescence. Findings need confirmation in larger samples.